Aquaculture Ecosystems: Adaptability and Sustainability - Saleem Mustafa (Penerbit UMS, 2015)
The book focuses on incorporating elements of adaptability and sustainability in aquaculture with a view to changing the course of development of the aquaculture industry towards an ecosystem approach. The book's contents have been structured to reflect the importance of forging synergies between aquaculture and other methods of seafood production. With the stagnation of capture fisheries, the future development of the aquaculture industry is vital to provide seafood security for the ever-expanding world population. The book synthesizes a huge wealth of information on current methods in aquaculture, drawing on best practices from established systems and identifying areas to be modified to facilitate a sustainable way forward. This exciting new book points to the importance of adopting new methods for the development of aquaculture models that can evolve in an environmentally compatible way. Detailed coverage is provided of the most important issues facing the growing aquaculture industry, including the biology and behavior of aquatic animals and their selection for use in aquaculture systems, integrated multi-trophic aquaculture, nutrient inputs and pollution, biofouling, blue carbon stocks in coastal aquaculture, climate change adaptations and knowledge management in aquaculture.